Does ESG Affect Credit Risk? - Ananta, Muhammad Adnan; Anwar, Mokhamad (Syntax Corporation, 2025)
Environmental, social, and governance (ESG) concerns became increasingly crucial for financial institutions, including banks, as they faced new types of risks associated with ESG factors. This study aims to investigate how these ESG dimensions affected non-performing loans (NPLs) in banks across ASEAN countries. With rising investor demand for sustainable practices and intensified regulatory pressures, incorporating ESG risks into risk management frameworks became imperative. This study uses panel data regression analysis along with the Chow and Hausman tests to assess the impact of ESG factors on NPL. The sample comprised banks from Indonesia, Malaysia, the Philippines, Singapore, and Thailand, selected based on Refinitiv Eikon's ESG values. The findings revealed that while environmental and governance performance had a statistically significant negative impact on NPLs, indicating that better environmental and governance practices were associated with fewer loan defaults, social performance showed a statistically significant positive effect on NPLs, suggesting that higher social scores correlated with increased loan defaults. This study highlighted the need for banks to carefully balance their social initiatives with financial stability and underscored the importance of integrating ESG factors into risk management strategies to enhance overall financial health and sustainability.